Prickly Defenders: A Review of Venomous Sea Urchins (Echinoidea) - Sina Ehlert-Flaskämper; Cherie A. Motti; Richard J. Harris (Marine Drugs, 2025)
Sea urchins, Echinoidea, are widely known for their defensive spines and pedicellariae, with some species having co-evolved venom in conjunction with those appendages. Despite this, their venomous arsenal remains poorly understood. Research has predominately focused on pedicellariae venom, while the spines have been largely neglected within studies. This review consolidates current knowledge of the venom systems (spines and pedicellariae) of sea urchins, focusing on the morphology, known venom components, and their functional effects. While early studies have established the bioactivity of crude extracts and fractions, along with the partial characterisation of some toxins, most of these studies are outdated and were conducted with very basic methodologies. Modern venomics presents an opportunity to meet this challenge, enabling development of a comprehensive database on venomous urchins and their toxins. This advancement will facilitate research into targeted early treatments and therapies for victims of sea urchin stings, ultimately improving health outcomes and enhancing our scientific understanding of venom toxins and their broader implications for human health and bioinnovation.